2018
DOI: 10.3390/su10072279
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Technical Efficiency of Sengcu Rice Producers through Better Financial Management and Sustainable Farming Practices in Mountainous Areas of Vietnam

Abstract: This paper analyzes the impacts of financial management and farming practices on the technical efficiency of Sengcu rice growers in Laocai, a mountainous province of Vietnam. The stratified random sampling method was employed to select 170 households representing two typical ecologies, lowland and upland. The structured questionnaire was applied to collect primary data through face-to-face interviews regarding current farming practices in the 2016-2017 growing seasons and farm-specific characteristics. The imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The same controversy has also been occurring in Vietnam. The series of following work, like Pham et al (2019), Bui et al (2018), Duong et al (2014), Lensink et al (2012), proved that better credit access enables to encourage the economic opportunities and enhances the living standard, and so forth. By contrast, Phan et al (2014) concluded that credit insignificant effects on income, and T. Dufhues (2007), Cuong (2008), Do Xuan et al (2016 proposed their critical reports that microcredit in Vietnam is designed for the poor and disadvantaged households but its performance serves mainly the non-poor groups.…”
Section: Introductionmentioning
confidence: 99%
“…The same controversy has also been occurring in Vietnam. The series of following work, like Pham et al (2019), Bui et al (2018), Duong et al (2014), Lensink et al (2012), proved that better credit access enables to encourage the economic opportunities and enhances the living standard, and so forth. By contrast, Phan et al (2014) concluded that credit insignificant effects on income, and T. Dufhues (2007), Cuong (2008), Do Xuan et al (2016 proposed their critical reports that microcredit in Vietnam is designed for the poor and disadvantaged households but its performance serves mainly the non-poor groups.…”
Section: Introductionmentioning
confidence: 99%
“…Existing literature suggests that natural disasters and pest infestations reduce output and increase the use of inputs in rice production, thereby negatively affecting technical efficiency [15,16] Technical efficiency refers to a farmer's capacity to attain the highest possible output utilizing existing and accessible technology [17,18]. Numerous studies have been conducted to examine the technical efficiency of rice production in Vietnam and the factors that influence it [4,[19][20][21][22][23]. However, there is a limited understanding of the effects of natural disasters and pest infestations on technical efficiency in rice production in Vietnam and how farmers overcome the consequences of these challenges.…”
Section: Introductionmentioning
confidence: 99%
“…The globalization of the economy and the increasing pace of informationization are both new development opportunities and great challenges for group enterprises [1][2][3]. The development of information technology has undoubtedly provided important technical support for shared financial services, making the financial information sharing resource base based on Internet information technology a new model of modern financial management [4][5][6][7]. Through financial shared resources, it can effectively innovate the financial process of enterprises, tap the management potential of enterprises, optimize resource allocation, help improve the management efficiency and creativity of enterprises, and promote the transition from accounting-based finance to management-based finance gradually.…”
Section: Introductionmentioning
confidence: 99%